2011
DOI: 10.5514/rmac.v37.i2.26137
|View full text |Cite
|
Sign up to set email alerts
|

El rol de los eventos antecedentes y consecuentes en la conducta sustentable

Abstract: Corral & Domínguez una posible alternativa para conectar la conducta proambiental individual con la práctica cultural de acciones sustentables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
0
7
0
5
Order By: Relevance
“…Equity is the action through which the individual comes into contact with people who have different conditions (ethnicity; age; sexual, religious, or political orientation; among others) and is related to behaviors of fair treatment and distribution of resources without bias, meaning not to give some people more than others based on their condition [22]. Equity also implies a balance between human wellness and ecosystem integrity, allowing people to access resources and preserve physical environment.…”
Section: Equitymentioning
confidence: 99%
“…Equity is the action through which the individual comes into contact with people who have different conditions (ethnicity; age; sexual, religious, or political orientation; among others) and is related to behaviors of fair treatment and distribution of resources without bias, meaning not to give some people more than others based on their condition [22]. Equity also implies a balance between human wellness and ecosystem integrity, allowing people to access resources and preserve physical environment.…”
Section: Equitymentioning
confidence: 99%
“…In the environmental context, they are generally studied as the cognitive dimension of environmental attitudes (Fishbein & Ajzen, 1975) and represent "opinions, thoughts or knowledge about the attitude object" (Hernández & Hidalgo, 2000, p. 310). In this line of investigation, studies have shown that environmental values and beliefs influence the adoption of sustainable lifestyles and environmental concerns (Axon, 2017;Corral-Verdugo & Guedea, 2011;Schultz et al, 2014).…”
Section: Values and Agroecological Beliefsmentioning
confidence: 99%
“…Intrinsic benefits are generated by the person through the practice of behaviours; these are psychological states that are experienced as pleasant and/or positive (such as happiness, satisfaction and pride) while the individual is engaging in the activity and once the activity is complete, and they can even be present prior to future engagement in that activity (Corral & Domínguez, 2011). It has been proposed that PEB can produce such psychological states (Corral, 2012;Corral-Verdugo, González-Lomelí, Rascón-Cruz, & Corral-Frías;Kasser, 2009).…”
Section: Intrinsic Benefitsmentioning
confidence: 99%
“…Los beneficios intrínsecos son generados por la propia persona a partir de la ejecución de su conducta; se trata de estados psicológicos que se experimentan como agradables y/o positivos (e.g., felicidad, satisfacción y orgullo) mientras el individuo realiza la actividad, una vez terminada, e incluso pueden presentarse previos a una próxima ejecución (Corral & Domínguez, 2011). Se ha propuesto que realizar CPA puede producir tales estados (Corral, 2012;Corral-Verdugo, González-Lomelí, Rascón-Cruz, & Corral-Frías;Kasser, 2009).…”
Section: Beneficios Intrínsecosunclassified
See 1 more Smart Citation